Ukraiński ruch kobiecy – Femen - Lesiewicz, Elżbieta (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2013)
The subject of consideration in this paper is the feminist movement Femen, which emerged in Ukraine in the early 21st century. The movement came into being under post-Soviet conditions, where the protection of women’s rights was marginal in the activities of women’s organizations operating at the time. This common, spontaneous movement was mainly initiated by young women, who struggle against violence using their own bodies in happenings and performance events. Half-naked women resort to the tactics of sextremism, protesting against violence directed at women, sex tourism, male domination and objectification of women. Their naked bodies are frequently displayed during demonstrations, with the intention of addressing issues that are frequently ignored by the authorities when traditional forms of protest are used. There are few places in the world where such protests have not taken place so far. The activities have stirred considerable controversy and provoked a public debate on the discrimination of women. Oppressed by the Ukrainian authorities, Femen activists moved to France in 2013.